In-Situ Epoxidation of Castor Oil Using Heterogeneous Acidic Ion-Exchange Resin Catalyst (IR-120) for Bio-Lubricant Application - Venu Babu Borugadda (Japanese Society of Tribologists, 2015)
The present work reports the formulation of castor oil (CO) epoxide as a bio-lubricant basestock. The main objective of this study was to improve the physico-chemical properties and thermo-oxidative stability of CO via structural modification. Epoxidation reaction was carried out at 60°C for 10 h using heterogeneous acidic ion-exchange resin (IR-120) as a catalysts (15mass%), acetic acid (0.5 mol) as an oxygen carrier and hydrogen peroxide (1.5 mol) as an oxygen donor. Product was confirmed by 1H-NMR, FTIR spectral analysis and epoxide content was determined by oxirane oxygen analysis. Further, significant physico-chemical properties such as viscosity, acid value (AV), pour point (PP) was determined for prepared CO epoxide. Thermo-oxidative stability of prepared epoxide and unmodified CO were compared by thermo gravimetric analysis (TGA) technique (in inert and oxygen atmospheres). Modified CO clearly illustrated significant improvement in the required physico-chemical properties and thermo-oxidative stability. Results of this study revealed that the prepared epoxide could be used as a potential bio-lubricant basestock in hydraulic lubricant application.